Antecedents of Fraud Prevention and Organizational Commitment as A Moderator - Anton Haryadi; Harnovinsah Harnovinsah; Syahril Djaddang (Journal Research of Social Science, Economics, and Management, 2026)
In the scope of the hospital business, the application system is required in running hospital operations, especially the application system to accommodate transactions that occur in the hospital, so it is also necessary to have an internal control structure and organizational commitment to reduce and even prevent the potential for fraud in these transactions. The focus of this research is to analyze the influence of application system variables, internal control structures and organizational commitment to Fraud Prevention. This research was conducted at group medical center hospitals using primary data, namely questionnaires filled out by respondents. The population in this study was 125 respondents and the sample used was 110 respondents. The analysis tools used are data quality tests, classical assumption tests and hypothesis tests using the help of SPSS version 25 application to process data. The results of the study prove that the variables of the application system do not have a significant effect on Fraud Prevention, the internal control structure has a significant effect on Fraud Prevention, the organization's commitment has a significant effect on Fraud Prevention, the effect of the organization's commitment in moderating the application system in full moderation to Fraud Prevention, the effect of the organization's commitment in moderating the internal control structure to Fraud Prevention moderate.